Adaptive fuzzy-based tracking control for nonlinear SISO systems via VSS and H∞ approaches. - Yeong-Chan Chang (IEEE Transactions on fuzzy systems)
An adaptive fuzzy-based tracking control equipped with VSS and H ∞ control algorithms is proposed for nonlinear SISO systems involving plant uncertainties and external disturbances. Both well-defined VSS indirect and direct adaptive fuzzy-based H∞ control schemes are developed. In order to compensate the effect of the approximation error via the adaptive fuzzy system on the H∞ tracking control, a modified algebraic Riccati-like equation must be solved and consequently it can be shown that all the states and signals of the closed-loop system are bounded and the effect of the external disturbance on the tracking error can be attenuated to any prescribed level. Compared with the previous literature that also addresses the adaptive fuzzy-based tracking control as in this paper, this paper can be extended to handle a larger class of uncertain nonlinear systems by the incorporation of robust VSS and H∞ control techniques. Finally, simulation examples are included to confirm the validity and performance of the proposed control algorithms